Functional assessment of autologous tissue expansion grafts for vaginal reconstruction in a rabbit model - Oliver Willacy; Nikolai Juul; August Olsen; Charlotte Egeland; Tu Hu; Mahboobeh Amoushahi; Thomas Jensen; Fatemeh Ajalloueian; Thomas Litman; Clara I. Chamorro; Magdalena Fossum (npj Women's Health)
Abstract This study explores a novel approach to vaginal reconstructive surgery using autologous tissue grafts, which may provide new therapeutic options for women with congenital or acquired vaginal anomalies. Using a small autologous vaginal tissue segment, we engineered a six-fold expanded graft perioperatively, leveraging the body as a bioreactor and avoiding preoperative tissue culture. In adolescent White New Zealand rabbits, a vaginal defect was created and repaired using a PLATE graft (perioperative, layered, autologous, tissue-expansion graft) containing mucosa, smooth muscle, collagen, and surgical mesh. After seven months, PLATE grafts were well integrated with native tissues, exhibited reduced fibrosis, and enhanced muscle regeneration compared to acellular grafts. Gene analysis revealed upregulation of smooth muscle and ECM organisation markers. Functional validation included successful breeding and vaginal delivery of live pups. PLATE grafts proved safe for vaginal reconstruction in rabbits, presenting a new direction in tissue engineering and expanding surgical options for women.